A (South) African voice on youth ministry research: Powerful or powerless? - Weber, Shantelle (HTS teologiese studies, 2015)
Research on youth ministry in Africa and specifically South Africa traces its origin to much research conducted in America and Europe. Many African scholars also draw on research and practices within these international spheres. Empirical research on youth ministry in Africa is however of great importance. For this purpose, comparative analysis research provides a research methodology in the social sciences that aims to make comparisons across different countries or cultures. A major problem in comparative research is that the data sets in different countries may not use the same categories, or define categories differently. This article makes use of a faith formation case study conducted in South Africa to highlight the value of this methodology when reflecting on international research from an African perspective. The main argument of this article is that international research on youth ministry is valuable in an African context but this research needs to be culturally contextualised through using comparative analysis as a research tool. This will reflect that there are many similarities between international youth ministry and the African context but there are also many cross-cultural disparities. After comparison, differences that are unique to the African context are noted. The article focuses on South Africa as a reflection of youth ministry within the broader African context.